SGLT1 Inhibition Attenuates Apoptosis in Diabetic Cardiomyopathy via the JNK and p38 Pathway - Lin, Na; Lin, Hui; Yang, Qi; Lu, Wenqiang; Sun, Zhenzhu; Sun, Shimin; Meng, Liping; Chi, Jufang; Guo, Hangyuan (Frontiers in Pharmacology, 2021)
Background: Recent studies have revealed that a novel selective sodium-glucose cotransporter 1 (SGLT1) inhibiton has shown beneficial effects in cardiovascular diseases. However, the question of whether SGLT1 inhibition influences diabetic cardiomyopathy (DCM) remains unanswered. In this study, we investigated the influence and underlying mechanism of SGLTI inhibition on DCM. Methods: SGLT1 levels were measured in diabetic patients with similar conditions who visited our hospital from January to December 2019. Wistar male rats (n = 50) were divided into five groups: control, diabetes induced by streptozotocin infusion, and diabetes treated with 0.5, 1.0, or 1.5 mg/kg mizagliflozin via stomach gavage for 12 weeks. H9C2 cardiomyocytes were treated with mizagliflozin and then exposed to a high glucose concentration (30 mmol/L). TUNEL assays were performed, and bcl2, bax, p-p38, p-Erk, p-JNK and caspase-3 levels were measured. We used siRNA and an SGLT1 overexpression plasmid to detect the effects of SGLT1. Results: SGLT1 levels were significantly elevated in DCM patients, and receiver operating characteristic (ROC) curve analysis identified SGLT1 as influencing DCM. The area under the curve (AUC) was 0.705 (p < 0.05), with 65.8% sensitivity, and 62.2% specificity. SGLT1 inhibition appeared to attenuate apoptosis in DCM via the JNK and p38 pathway. Conclusions: SGLT1 can be used as a marker for the diagnosis of DCM, and SGLT1 inhibition can attenuate apoptosis, thereby suppressing DCM development via the JNK and p38 pathway.